Causal Loop Diagram as Approaching Model Analysis in Increasing the Waste Volume at the Covid19 Pandemic Period - Muhammad Rifaldi; Muhammad Zid; Bagus Sumargo (JURNAL KESEHATAN LINGKUNGAN, 2021)
Introduction: The current Covid19 pandemic has overgrown, as reported statistics show. It causes multiple effects in human life, which one a majority of them doing all activities from home that increase the domestic waste production. The inadequate conventional handling management and a large amount of waste generated thrown away by open dumping. Methods: This study was carried out with a descriptive qualitative approach to describe all information of a good understanding in implementing a waste management system in Bekasi Regency. Mapping and identifying all the waste management process variables were then arranged dynamically using the Causal Loop Diagram (CLD) techniques. Results and Discussion: It should be noted that the variables influence many other variables because the policies applied have much influence on other environments. In the formed CLD in this study, the Covid19 pandemic variable will directly affect 3 (three) other variables such as public consumption patterns, economic conditions, and waste volume. The limited land and high costs were the problems that will hinder the success in waste management in Bekasi Regency. Conclusion: The CLD model shows that the waste management process did not get much attention from the community and managers during this pandemic. The thing that is not being overseen is the increase in the volume of domestic waste because most people choose to work from home, school holidays, and many outside activities are reduced. This CLD model shows that it is necessary to immediately improve waste management so that all waste that enters the landfill can be appropriately processed.